Reapp: Uma Ferramenta Cocriada com Instituições Sociais para o Fortalecimento do Terceiro Setor - Reis, Gabriel Belo Pereira dos; Rabelo, Gabriel Bastos; Gomes, André Gabriel Costa; Soares Neto, Carlos de Salles; Galabo, Rosendy (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
Sustainability and donor engagement represent constant challenges for Civil Society Organizations (CSOs) in Brazil, whose digital tools often lack participatory governance models. This work presents Reapp, a mobile and web platform that operates as a social network to connect donors and NGOs, aiming to enhance transparency and fundraising. The tool’s distinctive feature lies in its origin from a Co-designed methodology, in which the NGO community itself actively participated in the development with the goal of transforming the platform into a digital commons. As a result, the application has already supported several institutions in Maranhão, benefiting thousands of families, and has demonstrated a sustainable and scalable operational model. The article contributes by presenting not only a functional tool, but also a replicable model of civic technology development that integrates social innovation and community governance, offering new perspectives for strengthening the Third Sector.